Intracranial Ependymoma: Long-Term Results in a Series of 21 Patients Treated with Stereotactic (125)Iodine Brachytherapy - El Majdoub, Faycal (Public Library of Science, 2012)
BACKGROUND: We evaluated the long-term outcome in patients harboring intracranial ependymomas treated with interstitial brachytherapy (IBT). METHODS: Twenty-one patients (M/F = 9/12; median age: 29 years; range: 8–70 years), diagnosed with intracranial ependymoma (1 WHO I, 11 WHO II, 9 WHO III) were treated with IBT using stereotactically implanted (125)Iodine seeds between 1987 and 2010, either primarily, as adjuvant therapy following incomplete resection, or as salvage treatment upon tumor recurrence. Sixteen of 21 patients underwent microsurgical resection prior to IBT; in 5 patients, IBT was performed primarily after stereotactic biopsy for histological diagnosis. The cumulative tumor surface dose ranged from 50–65 Gy treating a median tumor volume of 3.6 ml (range, 0.3–11.6 ml). A median follow-up period of 105.3 months (range, 12.7–286.2 months) was evaluated. RESULTS: Actuarial 2-, 5- and 10-years overall- and disease-specific survival rates after IBT were each 90% and 100% at all times for ependymomas WHO I/II, for anaplastic ependymomas WHO III 100%, 100%, 70% and 100%, 100%, 86%, respectively. The neurological status of seven patients improved, while there was no change in 12 and deterioration in 2 patients, respectively. Follow-up MR images disclosed a complete tumor remission in 3, a partial remission in 12 and a stable disease in 6 patients. Treatment-associated morbidity only occurred in a single patient. CONCLUSIONS: This study shows that stereotactic IBT for intracranial ependymomas is safe and can provide a high degree of local tumor control. Due to the low rate of side effects, IBT may evolve into an attractive alternative to microsurgery in ependymomas located in eloquent areas or as a salvage treatment.